Legal Implications for Cooperative Legal Entities That Have Been Declared Bankrupt by the Commercial Court - Hakim, Luqman; Istiyanti, Erni (Eastasouth Institute, 2024)
Problems in cooperatives are often in the management of cooperatives and businesses. This problem is because until now many cooperatives are managed by people who are not professional in their fields, so that the progressiveness of cooperatives is difficult to develop. The purpose of this study is to determine the legal implications of the Cooperative legal entity declared bankrupt by the Commercial Court. The research method used is normative legal research, namely legal research by examining legal data sourced from the literature related to the literature related to the topic of this research. The results of this study are the legal consequences of a legal entity being declared bankrupt by the Commercial Court, including: a) Bankruptcy against a Cooperative does not necessarily end with the liquidation and dissolution of the Cooperative legal entity; b) Cooperatives can still carry out legal activities; c) The curator specified in the bankruptcy decision shall immediately be tasked with administering and controlling the bankruptcy estate; d) Actio Paulina applies; c) The lease can be terminated; and d) Employees may be terminated (PHK).